2014
DOI: 10.1517/17425247.2014.894504
|View full text |Cite
|
Sign up to set email alerts
|

Optimised nanoformulation of bromocriptine for direct nose-to-brain delivery: biodistribution, pharmacokinetic and dopamine estimation by ultra-HPLC/mass spectrometry method

Abstract: (2014) Optimised nanoformulation of bromocriptine for direct nose-to-brain delivery: biodistribution, pharmacokinetic and dopamine estimation by ultra-HPLC/mass spectrometry method, Expert Opinion on Drug Delivery, 11:6, 827-842,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Results of this study prove the findings in previous reports that CS was a good permeation enhancer for intranasal administration. The findings were also in line with the previous reports that intranasal administration of drug would preferentially deliver the drug to the brain by bypassing the BBB through the unique connection between the nose and the CNS …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Results of this study prove the findings in previous reports that CS was a good permeation enhancer for intranasal administration. The findings were also in line with the previous reports that intranasal administration of drug would preferentially deliver the drug to the brain by bypassing the BBB through the unique connection between the nose and the CNS …”
Section: Resultssupporting
confidence: 92%
“…The findings were also in line with the previous reports that intranasal administration of drug would preferentially deliver the drug to the brain by bypassing the BBB through the unique connection between the nose and the CNS. [30,31] Brain targeting parameters of the CD/CS-SCU-NPs A comparison of the brain targeting parameters was conducted on the CD/CS-SCU-NPs after intranasal and oral administration and on the SCU-SL after intranasal administration. Table 2 shows the targeting parameters calculated from the pharmacokinetic parameters in Table 1.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…Recently, BCT loaded in chitosan nanoparticles showed higher concentration in brain as investigated by Shadab and coworkers. [18] Esposito et al demonstrated the potential of lipid nanocarriers to improve the therapeutic effects of the BCT for Parkinson's disease. [19] Chitosan gel mediated delivery of BCT revealed the effectiveness of transdermal route as an alternate to oral delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ever growing attention has been focused to the intranasal administration route because it constitutes a non invasive method to bypass the BBB, enabling the delivery of both small-and macro-molecules to the CNS [6]. With respect to the PD treatment, actually nanocarriers loaded with L-Dopa or DA receptor agonists for systemic direct nose-to-brain delivery have previously been evaluated using CS NPs [4,52]. Instead, the intranasal delivery of DA-loaded NPs has not been previously evaluated.…”
Section: Discussionmentioning
confidence: 99%